Erosive and ulcerative lesions of the oral mucosa: a literature review (Research, Society and Development, 2022)
Oral pathology has a negative effect on the patient's quality of life and well-being. Ulcerative lesions of the oral mucosa consist of a group of entities with high recurrence and prevalence. In most cases, these types of lesions present painful symptoms to the patient, due to the loss of continuity of the oral epithelium, generating exposure of the nerve endings. The level of discomfort reported by the patient affected by ulcers is variable and depends on the clinical and histopathological characteristics of the lesion present in the oral mucosa. In view of the above, this study aimed to review the literature on erosive and ulcerative lesions of the oral mucosa, highlighting its clinical presentation, diagnosis and treatment, as well as the importance of correct clinical management in patients who have such lesions in the oral cavity. For the construction of this article, a bibliographic survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, using the Mendeley reference manager. The articles were collected from February to June 2022 and included between the years 2015 to 2022. Ulceration in the oral cavity represents a gap in the total thickness of the epithelial lining. They have many causes for the involvement of oral ulcers and the diagnosis still represents a challenge for most dentists. In this sense, the anamnesis must be carried out in a detailed and thorough manner. The results of this research reveal four main manifestations in the oral region, namely, traumatic ulcer, recurrent aphthous lesion, erythema multiforme and necrotizing sialometaplasia. Considering the high rates of these injuries, it is extremely important that health professionals are familiar with the complications arising from cancer treatments.